Do non-banks need access to the lender of last resort? Evidence from fund runs - Johannes Breckenfelder; Marie Hoerova (European Central Bank (ECB), 2023)
Are central bank tools effective in reaching non-banks with no access to the lender-of-last-resort facilities? Using runs on mutual funds in March 2020 as a laboratory, we show that, following the announcement of large-scale purchases, funds with higher ex ante shares of assets eligible for central bank purchases saw their performance improve by 3.6 percentage points and outflows decrease by 61% relative to otherwise similar funds. Following central bank liquidity provision to banks, the growth rate of repo lending to funds by banks more exposed to the system-wide liquidity crisis was up to five times higher compared to other banks.
Keywords: E58; G01; G10; G21; G23; 330; Investment funds; lender of last resort; market maker of last resort; asset purchases; COVID-19 liquidity crisis